1993
DOI: 10.1007/bf00553461
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of natural populations ofDryas iulia (Lepidoptera: Nymphalidae) revealed by enzyme polymorphism and mitochondrial DNA (mtDNA) restriction fragment length polymorphism (RFLP)

Abstract: Dryas iulia appears to have undergone a mode of evolution different from that of other members of its subfamily (Heliconiinae). While other species constitute highly subdivided and inbred populations, those of D. iulia are thought to be large and uniform. Analyzing six samples from Southern Brazil (state of Rio Grande do Sul) in relation to three enzyme systems (EST, LAP, and PGM) and their mtDNA RFLP patterns, we found that they are very similar at the molecular level. The F statistics for enzyme polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…Conversely, loci known to be under strong selection give widely divergent estimates of migration rate. However, good agreement among different types of genetic markers is far from routine (e.g., see Haag et al 1993). It must be acknowledged that the kind of detailed analysis of the biasing role of selection on measured gene flow estimates, as considered by Ross et al (1999), is very rarely undertaken, Most of the estimates that we have found did not investigate whether selection was acting upon any of the loci.…”
Section: Gene Flow Among Populationsmentioning
confidence: 89%
“…Conversely, loci known to be under strong selection give widely divergent estimates of migration rate. However, good agreement among different types of genetic markers is far from routine (e.g., see Haag et al 1993). It must be acknowledged that the kind of detailed analysis of the biasing role of selection on measured gene flow estimates, as considered by Ross et al (1999), is very rarely undertaken, Most of the estimates that we have found did not investigate whether selection was acting upon any of the loci.…”
Section: Gene Flow Among Populationsmentioning
confidence: 89%
“…Females were also found to move further in Pmclossiana eunomia (Barascud et al, 1999). In Boloria aquilonaris on the other hand, males travelled larger distances (the maximum being 1270 m (Mousson, Neve & Baguette, 1999), as was the case with Dryas iulia (Haag, de Araujo & Zaha, 1993) where males were thought to disperse five times more than females. Mark-release-recapture studies rarely detect long distance movements, so these figures as dispersal estimates are inevitably too small.…”
Section: Portugal Imentioning
confidence: 94%
“…In butterflies, as in other organisms, the nature and extent of gene flow is largely dependent on the mobility of individuals. Species with high vagility may disperse over large distances and therefore have extensive gene flow over large areas resulting in more homogeneous populations [5-8], whereas in species with low vagility, the effect of restricted dispersal will be evident at fine spatial scales [9-11]. Furthermore, gene flow may also be affected by a variety of ecological factors such as mating habits, gender-biased dispersal, diet specialization, habitat and population persistence, environmental factors and geographic distance [12].…”
Section: Introductionmentioning
confidence: 99%